Studi Eksegesis tentang “Tubuhmu adalah Bait Roh Kudus” Berdasarkan Teks 1 Korintus 6:19 - Purba, Jouth Jacoeb Hasian; Pardosi, Milton Thorman (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to analyze the understanding of Christianity and the meaning of “the body is the temple of the holy spirit” based on 1 Corinthians 6:19. The method used is qualitative research. The results reveal that the body of believers has been sanctified by Christ, becoming a new creation, and that the old man has been cleansed to live in holiness towards eternal life. Holiness itself is a sacred value that is closely attached to the temple because God is holy, so His presence makes the temple holy. Just as holiness is attached to the physical temple, so too is holiness obligatory in the spiritual temple, which is the body of believers. Throughout the Bible, from the Old Testament to the New Testament, holiness is always expressed as a central theme, both explicitly and implicitly. Holiness is not only relevant in the past, but also in the present and the future, because holiness stems from God's holy nature, so everything related to Him must also be holy. To be sanctified, then, means to be set apart and set apart for God.